MIKROENKAPSULASI Spirulina platensis DENGAN MENGGUNAKAN KITOSAN UNTUK MENINGKATKAN STABILITAS KADAR FIKOSIANIN - Fasusari, Cindy; Darmanto, YS; Rianingsih, Laras (Jurnal Pengolahan dan Bioteknologi Hasil Perikanan, 2013)
Spirulina platensis (S. platensis) is a blue-green microalgae (blue green algae). S.platensis has long been consumed as a food and a natural source of blue dye. The content ofblue pigment (phycocyanin) reached 20% of the dry weight. This research aims to determinewhether there is any effect of the addition of chitosan as enkapsulan at microencapsulationprocess of S. platensis on stability phycocyanin levels.Â The material used in this research is Spirulina platensis powder obtained from BPAPJepara. Enkapsulan materials used chitosan powder and solvent is 2% acetic acid obtainedfrom CV. Chemmix Pratama Bantul. The main parameters in this research were phycocyaninlevels, solved solids levels, and water content, while supporters are characterizing CapsulesS. platensis.Experimental design used in the preliminary research was Completely RandomizedDesign, while in the main study used a Group Randomized Design with a split plot in time,in which the plot is various types of samples S. platensis dry with 3 level while sub plot isthe treatment of storage time, the before storage time, second days, fourth day, sixth days ,and eighth days. Each treatment was repeated three times .Data factors were analyzed usinganalysis of variance. To find the difference between treatments was tested with test dataHonestly Significant Difference (HSD).The results showed that the addition of different chitosan concentration on Spirulinaplatensis at microencapsulation exert a highly significant (p <0.01) in phycocyanin levels,levels of dissolved solids, and water content. Best quality Spirulina platensis shown inaddition to the value of 5% chitosan content of 4.80% phycocyanin. While the bestphycocyanin levels found in samples after storage B (5%). In the SEM image results,Spirulina platensis which microencapsulation with chitosan has a more rounded structure andcompact compared to Spirulina without coating material.